Proposal of Evaluation Protocol for Measuring Citizen Sensibilisation in Recycling Practices - Quiroz-Moreno, J; Santander-Tapia, P; Delgado-Cadena, L (Springer Nature, 2024)
Recycling is one of several key activities proposed under a circular economy to keep raw materials in use. However, despite the importance of recycling, there are currently low recycling rates for some materials, such as plastic, glass and tyres. In this context, citizen education and awareness is essential, so new forms of awareness-raising, such as virtual or immersive experiences, are being explored in order to support the awareness-raising process. It is for this reason that this research proposes, based on a literature review, a conceptual evaluation protocol that allows evaluating the degree of learning/awareness of citizens in relation to recycling, thanks to their interaction with virtual experiences or other traditional learning techniques. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2024.